2018
DOI: 10.5734/jgm.2018.15.2.72
|View full text |Cite
|
Sign up to set email alerts
|

Korean physicians’ attitudes toward the prenatal screening for fetal aneuploidy and implementation of non-invasive prenatal testing with cell-free fetal DNA

Abstract: Physicians' attitudes may have a strong influence on women's decision regarding prenatal screening options. The aim of this study is to assess the physicians' attitudes toward prenatal screening for fetal aneuploidy including non-invasive prenatal testing (NIPT) in South Korea. Materials and Methods: Questionnaires were distributed and collected at several obstetrics-gynecological conferences and meetings. The questionnaire included 31 multiple choice and 5 fill-in-the-blank questions. Seven questions requeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In South Korea, maternal serum screening test for fetal aneuploidy in the first trimester has been covered by the NHIS and performed in more than 95% of pregnancies. 17 Whereas, termination of pregnancy including DS pregnancy was designated as a crime and was subject to punishment by criminal law and a physician only to perform a termination in exceptional cases under the Maternal and Child Health law. 18 It is difficult to provide legal data on artificial abortion of DS pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, maternal serum screening test for fetal aneuploidy in the first trimester has been covered by the NHIS and performed in more than 95% of pregnancies. 17 Whereas, termination of pregnancy including DS pregnancy was designated as a crime and was subject to punishment by criminal law and a physician only to perform a termination in exceptional cases under the Maternal and Child Health law. 18 It is difficult to provide legal data on artificial abortion of DS pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the role of nurses as advocates is now increasingly emphasized [21]. Although a study attempted to examine the proper clinical applications and nursing implications of NIPT at the initial stage of the introduction of NIPT in Korea [22], since then, only one study has examined healthcare providers' attitudes toward NIPT and its implementation [23]. To our best knowledge, there are yet no studies on pregnant women's NIPT-related experiences in Korea.…”
Section: Summary Statementmentioning
confidence: 99%
“…Our survey on fetal health screening in Europe and other developed countries has shown that screening is offered to all pregnant women in Belgium, Denmark, Finland, France, Switzerland, South Korea, etc., and the expenses are reimbursed (11,12). Table 1 shows the uptake rate of prenatal screening in 18 countries.…”
Section: Prenatal Screening Uptake Rates and Its Worldwide Trendsmentioning
confidence: 99%